MODERN COMMEMORATIVE PRACTICES AS A INSTRUMENT FOR SHAPINGTHE FOREIGN POLICY IDENTITY OF THE RUSSIAN FEDERATION (Вісник: Міжнародні відносини, 2025)
Background. The 2025 «victory parade» on Red Square in Moscow was a practical embodiment of Russia's commemorative practices, as it brought together numerous foreign leaders from different regions for the first time since the start of the aggression against Ukraine, demonstrating a shift in geopolitical balances and the mechanism of constructing foreign policy identities from Russia and EU countries to the «Global South».Methods. The constructivist analysis method was used to reveal how collective memory practices influence the formation of the Russian Federation's foreign policy identity. The main method is the analysis of the discourse of official rituals, commemorative dates, mass celebrations with the participation of representatives of other states, and symbolic acts. In addition, a comparative analysis of commemoration in different countries is used to identify the unique characteristics of Russian state practices. The method of content analysis of official events, speeches, and news about places and actions of remembrance provides insight into the mechanism of legitimising the external positioning of the Russian Federation.Results. Commemoration has become a tool for Russia to promote its image as a «liberator from neo-Nazism» and overcome international isolation. For this purpose, Russia is involving China, North Korea and countries of the Global South in its anti-Western narrative. The participation of European leaders from Slovakia and Serbia, which are involved in the integration process, highlights pragmatic motives related to economic benefits or historical memory, but does not form a cohesive alliance. Despite managing to reestablish a certain international presence at the 2025 parade compared to previous years, Russia has been unable to change the global discourse on its aggression against Ukraine. The diplomatic opposition of Ukraine and the EU contributes to this.Conclusions. The 2025 «victory parade» was not an expression of broad support for Russia, but rather a tool for selective norm-setting and the formation of foreign policy identity, underscoring the fragmentation of the international order and the limitations of Russian normative power.Вступ. «Парад перемоги» 2025 на Красній площі в Москві став практичним втіленням комеморативних практик Росії, адже уперше з початку агресії проти України зібрав велику кількість іноземних лідерів із різних регіонів, що засвідчує зміну геополітичних балансів і дію механізму конструювання зовнішньополітичних ідентичностей від Росії та країн ЄС до «Глобального Півдня».Методи. Було використано метод конструктивістського аналізу, що дозволяє розкрити, як практики колективної пам’яті впливають на формування зовнішньополітичної ідентичності Російської Федерації. Основним методом є аналіз дискурсу офіційних ритуалів, пам’ятних дат, масових святкувань за участі представників інших держав та символічних актів. Додатково застосується порівняльний аналіз комеморації в пострадянських країнах для виявлення унікальних характеристик російських державницьких практик. Метод контент-аналізу офіційних заходів, промов, новин щодо місць та дій вшанування пам’яті дозволяє простежити механізм легітимації зовнішнього позиціювання РФ.Результати. Комеморація стала інструментом Росії для просування образу «визволителя від неонацизму» та подолання міжнародної ізоляції. З цієї метою Росія залучає Китай, КНДР і країни Глобального Півдня до антизахідного наративу. Участь європейських лідерів Словаччини та Сербії, яка залучена в інтеграційний процес, підкреслює прагматичні мотиви, пов’язані з економічними вигодами чи історичною пам’яттю, але не формує цілісного альянсу. Зважаючи на те, що вдалось відновити певну міжнародну присутність на параді 2025 року, порівняно з минулими роками, Росія не змогла змінити глобальний дискурс про агресію проти України. Цьому сприяє дипломатична протидія України та ЄС.Висновки. «Парад перемоги» 2025 року був не вираженням широкої підтримки Росії, а інструментом вибіркового нормотворення та формування зовнішньополітичної ідентичності, що підкреслює фрагментованість міжнародного порядку та обмеженість російської нормативної сили.
Keywords: commemorative practices; constructivism; foreign policy identity; international subjectivity; Russian Federation; Ukraine; European Union